Semantic Web services theory, tools and applications - Cardoso 1970- (Information Science Reference, 2007)
"This book brings together researchers, scientists, and representatives from different communities to study, understand, and explore the theory, tools, and applications of the semantic Web. It joins the semantic Web, ontologies, knowledge management, Web services, and Web processes into one fully comprehensive resource, serving as the platform for exchange of both practical technologies and research"--Provided by publisher.